Daratumumab in first-line treatment of patients with light chain amyloidosis and Mayo stage IIIb improves treatment response and overall survival - Oubari, Sara; Hegenbart, Ute; Schoder, Renate; Steinhardt, Maximilian; Papathanasiou, Maria; Rassaf, Tienush; Thimm, Andreas; Hagenacker, Tim; Naser, Eyad; Duhrsen, Ulrich; Reinhardt, Hans C.; Kortum, Martin; et al. (Haematologica, 2024)
Treatment of patients with Mayo stage IIIb light chain (AL) amyloidosis is still challenging, and the prognosis remains very poor. Mayo stage IIIb patients were excluded from the pivotal trial leading to the approval of daratumumab in combination with bortezomib-cyclophosphamide-dexamethasone. This retrospective, multicenter study evaluates the addition of daratumumab to first-line therapy in patients with newly diagnosed stage IIIb AL amyloidosis. In total, data from 119 consecutive patients were analyzed, 27 patients received an upfront treatment including daratumumab, 63 a bortezomibbased regimen without daratumumab, eight received therapies other than daratumumab or bortezomib and 21 pretreated patients or deceased prior to treatment were excluded. In the daratumumab group, median overall survival was not reached after a median follow-up time of 14.5 months, while it was significantly worse in the bortezomib- and the otherwise treated group (6.6 and 2.2 months, respectively) (P=0.002). Overall hematologic response rate at 2 and 6 months was better in the daratumumab group compared to the bortezomib group (59% vs. 37%, P=0.12, 67% vs. 41%, P=0.04, respectively). Landmark survival analyses revealed a significantly improved overall survival in patients with partial hematologic response or better, compared to non-responders. Cardiac response at 6 months was 46%, 21%, 0% in the daratumumab-, bortezomib- and otherwise treated groups, respectively (P=0.04). A landmark survival analysis revealed markedly improved overall survival in patients with cardiac very good partial response vs. cardiac non-responders (P=0.002). This study demonstrates for the first time the superiority of an upfront treatment with daratumumab over standard-of-care in stage IIIb AL amyloidosis.
Vorab veröffentlicht: 13. Juli 2023
Gesehen am 06.05.2024